Investigation of Wind Energy to Generate Electric Power and its Role to Reduce Environmental Pollution in Iraq - Kareem Ameen, Shadan; Saeed Sedeeq, Murad; Bolatturk, Ali (International Journal of Engineering and Technology, 2018)
Wind energy is one of the renewable energy that has been widely used round the world which is abundant, renewable, and generally available. The present paper established to study the possibility of generating electric power by wind turbines for three important cities in Iraq located in terms of altitude from sea level and climate, namely (Mosul in north, Baghdad in middle and Basra in the south of Iraq). The calculations depend on the hourly meteorology data’s like wind speed, wind direction and air temperature taken from (Iraqi meteorological organization and seismology) since 2005 to 2015. Noting that, the calculations had been done for three variable types of wind turbine found in global markets which differ in capacity, cut-in velocity, cut-off velocity, blade diameter and initial cost. The main aims for present paper can be divide in three stages. First, it studies the possibility of using wind turbines for the selected cities. Then, it estimates the amount of annual electric power generation (EPG) and it’s contribution to minimize the environmental pollution if the same power generated by gas turbine which regarded the diffuse method in Iraq. Finally, an economic analysis is also carried out for each turbine. Life cycle assessment software (SimaPro V 7.2) has been used to obtain the amount of emissions produced per kWh electricity power by gas power plant. (P1-P2) method has been used to estimate the economic data’s for the project. The results of the research will decide the most appropriate zone to do the projects and the best turbine to give maximum EPG and its ability to reduce emissions with giving financial gain and payback period as an economic value to encourage the investors to apply like this project.